Socio-cultural correlates of food intake among pregnant women in Ijebu-east, South Western, Nigeria. (2012)
Maternal health and morbidity in Nigeria has generated series of concern among individuals, agencies and Government. The concern could be linked to the deplorable conditions pregnant women live, their poor dietary habits and low food intake before, during pregnancy and Lactation. Low intake of calories in pregnancy not only affects mothers’ health but also the child’s health Data was collected through Structured Questionnaire, Focus Group Discussions (FGDs) Observations and Indept Interviews. Manual content analysis of qualitative data was done. On the other hand, quantitative data were analyzed by descriptive and bi-variate techniques through the use of computer package for data analyzes (SPSS version 15.0) The findings shows that: Pattern of social relationships existing between family members like Mother- in-laws, parents, siblings, affine, cognates, members of religious group and neighbours have significantly influence nutritional intakes of women during pregnancy and lactation. That men’s choice of foods have significantly influence their wives’ choice of foods and eating patterns, before and during pregnancy. Like other Ijebu communities, there are limited culturally forbidden foods associated with pregnancy in Ijebu East. conclusion: The study offered an in-depth understanding into series of factors relating to maternal health and morbidity and food intake of pregnant women.